COVID-19 vaccine and booster hesitation around the world: A literature review - Shah, Aashka; Coiado, Olivia C. (Frontiers in Medicine, 2023)
The development of COVID-19 vaccines has helped limit the extent of the pandemic, which over the past 2 years has claimed the lived of millions of people. The Moderna and Pfizer COVID-19 vaccines were the first to be manufactured using mRNA technology. Since then, other manufacturers have built their own vaccines which utilize adenovirus vector, whole inactivated coronavirus, and protein subunit methods. Given the continued mutation of the SARS-CoV-2 virus, a booster of the COVID-19 vaccine offers additional protection for citizens, especially those with comorbid conditions. However, uptake of the vaccine and booster has faced hurdles. This literature review aims to analyze the acceptance of the COVID-19 booster among different populations throughout the world. Keywords searched include “COVID-19 vaccine rates OR COVID-19 booster rates,” “COVID-19 vaccine hesitancy,” “COVID-19 booster hesitancy,” “reasons against COVID-19 vaccine,” “reasons for COVID-19 vaccine,” and “COVID-19 vaccine acceptance” (for each country). Research articles indexed in PubMed, University of Illinois Urbana-Champaign Library, and Google Scholar were included. Despite the proven effectiveness of the COVID-19 booster, vaccine hesitancy is still causing suboptimal compliance to the primary vaccine and booster, thus slowing down control of the pandemic. Reasons for vaccine hesitancy differ by country and acceptance is affected by misinformation, political circumstances, and cultural values. Among the most common reasons found are distrust in the government, a lack of safety information, and fear of side effects. Uptake of the COVID-19 vaccine has also been delayed in low and middle income countries due to resource allocation and as a result, these countries have fallen behind vaccination benchmarks. The future of COVID-19 vaccination is unknown, but vaccine mandates and additional booster doses are a possibility. Determining the ethical impact that these policies could have will allow for the best implementation.